2014
DOI: 10.5539/jas.v6n8p131
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Pre-Emergence and Post-Emergence Soybean Herbicides for Control of Glufosinate-, Glyphosate-, and Imidazolinone-Resistant Volunteer Corn

Abstract: Glyphosate-resistant corn and soybean are grown in rotations in the Midwest, including Nebraska. Volunteer corn is a problematic weed in soybean fields because it causes harvest problems, reduces yield and seed quality, and potentially harbors insects, pests, and diseases. Several pre-packaged herbicides have been registered in soybean in recent years, but response of volunteer corn to these herbicides has not yet been documented. Greenhouse experiments were conducted to evaluate the response of glufosinate-, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 18 publications
1
27
0
1
Order By: Relevance
“…Chemical weed control is one of the methods used to control weeds in DSR, but due to concerns about the development of resistance and an insufficiency of new and effective herbicides, there is a need to integrate other weed management strategies along with chemical control (Chahal et al, 2014(Chahal et al, , 2015. Because of the variability in the growth habit of weeds, no single method of weed control can provide effective and season-long control in DSR (Aulakh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Chemical weed control is one of the methods used to control weeds in DSR, but due to concerns about the development of resistance and an insufficiency of new and effective herbicides, there is a need to integrate other weed management strategies along with chemical control (Chahal et al, 2014(Chahal et al, , 2015. Because of the variability in the growth habit of weeds, no single method of weed control can provide effective and season-long control in DSR (Aulakh et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Higher rates (≥ 2,480 g ae ha -1 ) were required to achieve 90% control of 20-cm tall common waterhemp plants. Several studies have reported that the height of weed species at the time of POST herbicide application is an important factor determining the level of control achieved (Chahal et al, 2014;Cordes et al, 2004;Craigmyle et al, 2013b). …”
Section: Common Waterhempmentioning
confidence: 99%
“…The association between chlorimuronethyl with other molecules, highlighting glyphosate, was recently studied by many authors, among who are Albrecht et al (2012), Oliveira Neto et al (2013), Chahal et al (2014) and Belfry et al (2015). These studies were directed especially for difficult to control weed management, and also to the selectivity of this association for soybean crops.…”
Section: Introductionmentioning
confidence: 99%